2023
DOI: 10.1002/fsn3.3677
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of goji berry processing and utilization

Jing Yu,
Yamei Yan,
Lutao Zhang
et al.

Abstract: Goji berry (wolfberry, Lycium), is a genus of Solanaceae, in which the roots, stems, leaves, and fruits are for both food and medicinal uses. In recent years, the demand for health food and research purposes has led to increasing attention being paid to the application of goji berry nutrients and resources. There are three general strategies to process and utilize the goji berry plant. First, the primary processing of goji berry products, such as dried goji berry pulp, and fruit wine with its by‐products. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Goji berry pulp is the fresh cloudy juice extracted from goji berries without the addition of any preservatives or chemicals. It is produced through a series of steps, including selecting, cleaning, crushing, pulping, filtering, and homogenizing the fresh goji berries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Goji berry pulp is the fresh cloudy juice extracted from goji berries without the addition of any preservatives or chemicals. It is produced through a series of steps, including selecting, cleaning, crushing, pulping, filtering, and homogenizing the fresh goji berries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lycium barbarum, a species of the genus Lycium within the Solanaceae family, is a perennial shrub primarily distributed in Ningxia, Xinjiang, Inner Mongolia, but is also found in other regions. The L. barbarum fruit is valued for its medicinal and culinary benefits, including its ability to lower blood pressure, nourish the kidneys and lungs, protect the liver, and replenish blood, as well as its whitening properties [1,2]. In recent years, L. barbarum has become increasingly popular on the market, leading to a continuous expansion of planting areas and the development of many high-yielding and high-quality varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Wolfberry (Lycium barbarum) is rich in active components with various biological activities, such as antioxidants, anticancer, immune system fortification, etc. , Polyphenols, one of the most important active ingredients in wolfberry, are considered to be crucial natural antioxidants . Research has demonstrated that polyphenols in wolfberry exist in two forms: free and bound .…”
Section: Introductionmentioning
confidence: 99%